Development and psychometric evaluation of the Brief Parenting Questionnaire - Kenneth E. Miller; Alexandra Chen; Ioannis Bakolis; Gabriela V. Koppenol-Gonzalez; Maguy Arnous; Fadila Tossyeh; Dalia Al-Ogaily; Mark J. D. Jordans (BMC Psychology)
Abstract Background There is a paucity of brief self-report parenting measures validated for use in low- and middle-income countries (LMICs). We developed the Brief Parenting Questionnaire (BPQ), a 24-item self-report measure for use with parents of children ages 3–12. Objective We describe the development and evaluation of the psychometric properties of the BPQ, which was designed to include two subscales: warm and responsive parenting (WRP) and harsh parenting (HP). Participants and setting The sample included an equal number of male and female caregivers (n = 480) from 240 families in North Lebanon that took part in a randomized controlled trial (RCT) of the Caregiver Support Intervention. Study participants were primarily Syrian (95.2%); others were Lebanese (4.2%) and Palestinian (0.6%). Methods The development of the BPQ is described. To assess its psychometric properties, we used data from the RCT for which the instrument was developed. Confirmatory factor analysis (CFA) was used to examine the factor structure of the BPQ. The reliability of the BPQ and its potential subscales was assessed by examining the internal consistency using Cronbach’s alpha and McDonald’s omega. Multi-group CFA was conducted to identify if the same two constructs were being measured across mothers and fathers. Results A two-factor model best fit the data, with 16 items loading on WRP and seven items on HP, corresponding to the two parenting dimensions the scale was designed to assess. Internal consistency was good: full scale ɑ=0.83, WRP ɑ=0.86, and HP ɑ=0.76. One item not loading on either subscale was retained for theoretical reasons. Conclusions The BPQ is a brief culturally grounded self-report measure of parenting validated for use with Middle Eastern Arabic speaking parents. The data for this paper come from a pre-registered trial: ISRCTN33665023.